2018
DOI: 10.1370/afm.2199
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Primary Care Practices in Studies of Improvement: Did You Budget Enough for Practice Recruitment?

Abstract: Recruitment of practices for large-scale practice quality improvement transformation initiatives is difficult and costly. The cost of recruiting practices without existing partnerships is expensive, costing 7 times more than reaching out to familiar practices. Investigators initiating and studying practice quality improvement initiatives should budget adequate funds to support high-touch recruitment strategies, including building trusted relationships over a long time frame, for a year or more.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…Although a cost-effectiveness analysis of the intervention was excluded in this review, Culler et al previously found practice facilitation to be cost-neutral while recent work from EvidenceNOW and the Healthy Hearts in the Heartland (H3), Fagnan et al, reported the total average costs of implementation to be $5529 per practice. 61,62 Overall, practice facilitation may further enhance quality improvement initiatives such as the patient-centered medical home (1.3% increase in preventive services) and care coordination (0.2 to 16.4% increase in cancer screening and 0.1 to 8.7% increase in diabetes screening), with electronic health records providing clinical decision support (42% increase in odds of preventive care processes). [63][64][65] Incorporating quality improvement, practice facilitation has a leading role in the transformation of care quality in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…Although a cost-effectiveness analysis of the intervention was excluded in this review, Culler et al previously found practice facilitation to be cost-neutral while recent work from EvidenceNOW and the Healthy Hearts in the Heartland (H3), Fagnan et al, reported the total average costs of implementation to be $5529 per practice. 61,62 Overall, practice facilitation may further enhance quality improvement initiatives such as the patient-centered medical home (1.3% increase in preventive services) and care coordination (0.2 to 16.4% increase in cancer screening and 0.1 to 8.7% increase in diabetes screening), with electronic health records providing clinical decision support (42% increase in odds of preventive care processes). [63][64][65] Incorporating quality improvement, practice facilitation has a leading role in the transformation of care quality in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple lessons learned in this study that could assist future efforts of implementation and dissemination research in primary care practices. Perhaps the key lesson learned was the need for additional time and resources for practice recruitment, 19,20 a conclusion reached by other EvidenceNOW cooperatives. There is also a need for a longer intense intervention phase where practices have ongoing interaction with external quality improvement specialists, including physician consultants.…”
Section: Discussionmentioning
confidence: 99%
“…PERCs were a key to recruitment success with EvidenceNOW: 1 in 3 practices had a prior relationship with the organizations enrolled, whereas only 1 in 20 did not. 13 Practices and communities value the sustained relationship, noting that "ORPRN was here yesterday, today and will be with us tomorrow" (personal communication, Lyle Fagnan, MD, 2018). Sustaining these relationships is a major challenge as grants and contracts do not support the need to maintain continuity between projects.…”
Section: Oregon: Practice Enhancement Research Coordinatorsmentioning
confidence: 99%